Salmonella infection in chickens: pathogen, pathogenesis, and dietary non-drug feed additives as alternatives to antibiotics — a comprehensive review - Nahed A. El-Shall; Mehmet Cemal Adiguzel; Wafaa A. Abd El-Ghany; Walaa A. Gamal (Folia Microbiologica, 2026)
Salmonella infections in poultry can result in systemic, localized diseases, or prolonged asymptomatic carriers. Avian host-specific Salmonellae such as S. Pullorum and S. Gallinarum can spread vertically or horizontally from diseased birds or contaminated feed, water, or litter (fecal-oral route), resulting in significant mortality rates of up to 80% in chicks and poults during 1st 2–3 weeks of age. Furthermore, one of the most common food-borne diseases in humans is caused by Paratyphoid Salmonellae . The antibiotic overuse or misuse in animal production raises concerns due to the formation of resistant bacteria or genes and tissue residues. Currently, Salmonellae are among the most antibiotic-resistant bacteria and cause the most severe infections in both human and animals. Besides biosecurity, the inclusion of feed additives such as probiotics and their derivavtives, phytobiotics, nanoparticles, and egg yolk immunoglobulins can help to lessen the burden of Salmonella infections (colonization and shedding) in poultry and enhance health and immune response. Additionally, bacteriophages, the bacteria-specific viruses, are considered a biocontrol measure for Salmonella depending on using the appropriate phage, doses, time, and route of administration. These interventions have the potential to replace conventional antibiotics in therapeutic settings by exhibiting bactericidal effects without the risk of emerging antibiotic-resistant strains or intestinal dysbiosis. Moreover, the synergistic interactions between these interventions can provide a more inclusive, efficient, and integrated approach for managing Salmonellosis in poultry flocks. This current review aims to spotlight on the avian Salmonella infections and the role of antibiotic alternatives to control it.